2018
DOI: 10.1007/s13524-018-0714-3
|View full text |Cite
|
Sign up to set email alerts
|

Looking at Population Health Beyond “Male” and “Female”: Implications of Transgender Identity and Gender Nonconformity for Population Health

Abstract: Looking beyond binary measurements of “male” or “female” can illuminate health inequality patterns that correspond to gender identity rather than biological sex. This study examines disparities in overall health among transgender men, transgender women, gender-nonconforming adults, and cisgender (nontransgender) men and women in the U.S. population. Behavioral Risk Factor Surveillance System (BRFSS) data from 32 U.S. states and territories between 2014 and 2016 yield an analytic sample that identifies 2,229 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 71 publications
1
51
1
Order By: Relevance
“…Further, we sought to highlight the importance of classifying and examining the health of the transgender population as unique subpopulations versus one homogeneous population. Although previous research has identified significant differences in health-related individual factors and health outcomes between transgender and cisgender people [55][56][57][58], this study delineated the health differences among transgender subpopulations (groups) in order to identify transgender groups at greatest risk for poor health. Moreover, by acknowledging the heterogeneity of the transgender population, we fill gaps in knowledge about the health of TM and GNB adults, two transgender groups that have been underrepresented in contemporary empirical transgender health research.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we sought to highlight the importance of classifying and examining the health of the transgender population as unique subpopulations versus one homogeneous population. Although previous research has identified significant differences in health-related individual factors and health outcomes between transgender and cisgender people [55][56][57][58], this study delineated the health differences among transgender subpopulations (groups) in order to identify transgender groups at greatest risk for poor health. Moreover, by acknowledging the heterogeneity of the transgender population, we fill gaps in knowledge about the health of TM and GNB adults, two transgender groups that have been underrepresented in contemporary empirical transgender health research.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as population‐representative data on gender identity and sexual orientation become more widely available, demographers will be better able to describe families including members of gender and sexual minorities (Baumle, ). Studies of transgender individuals have already begun to appear in demographic journals (Lagos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Going forward, it seems likely that research on sexual minority populations will expand to include more studies of transgender populations (Liu & Wilkinson, ). New research on these topics, and publication in top disciplinary journals, will increasingly serve as indicators of societal acceptance of sexual minorities and movement beyond our usual binary conceptions of sex and gender in the family sciences (Lagos, ). Additional attention to parenting among sexual minorities is also needed in studies of family complexity that to date have largely focused on heterosexual populations as changing reproductive technologies provide new opportunity for childbearing and parenting in a variety of union contexts.…”
Section: Research Themesmentioning
confidence: 99%